Cultural Concepts of Substance Use and Idioms of Distress in Male Syrian Refugees in Germany. (30th September 2020) - Lindert, J; Neuendorf, U; Schaefer, I
Abstract: Background: The study of substance use disorder among communities affected by mass violence has not received equal attention as other health concerns. This has led to the majority of psychosocial interventions in post-conflict zones being unresponsive to substance use-related problems among refugees. This study focused on gaining an in-depth understanding of the lay discourses and cultural concepts around substance use among male Syrian refugees in Germany. Methods: Purposive and convenience sampling strategies were used for the recruitment of participants. The interview schedule was piloted among experts prior to conducting fieldwork. Inclusion criteria were a recent arrival from Syria. The study utilized a qualitative methodology, consisting of semi-structured group interviews with a native-speaking professional translator. The interviews were audio-recorded, transcribed and analyzed using an inductive thematic approach. Results: Participants were refugees aged between 18 - 60 years (n = 19). The narratives revealed three themes. Firstly, the characteristics of Syrian society featured particularly in the participants' narratives. Society's rejection of substance use, generally enforced through taboos (e.g. halal/haram) was described and placed in contrast to a more liberal German society. Easier access and an open attitude to drug use in Europe were seen as problematic by some. The social stigma attached to mental health issues was discussed in participant narratives. Stigma was interpreted as both a cause for the development of a disorder as well as an exacerbating factor. Family was perceived as a protective force against substance use and the development of disorders. Thirdly, substance use was understood as one strategy of coping with stress, experience of violence and displacement. Conclusions: Substance use may be seen as both an expression and a product of social suffering caused by the experience of war and displacement.